Master Momik: an Architect, Sculptor and Miniaturist (On Iconographic Features of Some of His Artworks) - Danielyan, Inesa G. (Actual Problems of Theory and History of Art, 2016)
The miniature and sculptural creations of the famous Armenian medieval master Momik (13th– 14th centuries) have a distinguishable iconography. is is particularly evident with the images of the Holy Apostles and the Evangelists. The portraits of evangelist Mark with Apostle Peter and Prochorus presented without John show a special appreciation of the “teachers and disciples” images that can be associated with the foundation and the activities of the famous University of Gladzor.The third Khachkar (crosstone) of Momik also has a unique iconography. Khachkar was erected by the behest of Syunik — princess Tamta before 1312. Here, among the twelve apostles, the master highlights the portraits of Peter and Andrew writing only their names. As we know, Apostle Peter is venerated as the founder of the Western Church and Andrew as the founder of the Eastern Churches. This interpretation may have been in uenced by the religious controversy for association of churches in the Armenian kingdom of Cilicia, to which there was an opposition in Syunik. It is possible to assert that Momik’s artworks bear the imprint of cultural, religious and political events of that time.
Keywords: Momik; khachkar; Evangelist Mark; Prochorus; Apostle Peter; Apostle Andrew